Understanding the impact of Artificial Intelligence on physician-patient relationship: a revisitation of conventional relationship models in the light of new technological frontiers - Greco, Francesca; Picozzi, Mario (Medicina Historica, 2022)
The physician-patient relationship has undergone a transition throughout the ages. The introduction of Artificial Intelligence (AI) in recent years, however, is redefining this relationship. The four main relationship models described by Emanuel in 1992 are known as paternalistic, informative, interpretive, and deliberative. The aim of this study is to understand how conventional models of doctor-patient relationships are changing when considering the impact AI has on medical practice.The introduction of AI could strengthen the physician's role resulting in the so-called digital paternalism or even undermining the physician's role.Also, doctors and patients could experience decision paralysis when AIs’ recommendations are difficult to understand or explain to patients and it may affect the organizational aspects of healthcare contexts. It becomes necessary to define the source of the information presented to the patient.On another hand, AI could increase the patient's trust in the doctor by knowing that various therapeutic choices are being discussed and fully explained.It’s complicated to understand whether the trust relationship established between doctor and patient remains bi-univocal, by incorporating AI in the clinician’s figure, or whether AI must be introduced as a separate entity implying an asymmetry in this relationship.Shared decision-making, guidelines and training, together with an effort in communication are fundamental to best incorporate AI into clinical practice. It is relevant to educate doctors on the new models of relationships that can be created, in addition to studying patient populations within the context of these models’ framework.